Experimental selection of long‐term intracellular mycobacteria - Vazquez, Cristina Lourdes; Lerner, Thomas R.; Kasmapour, Bahram; Pei, Gang; Gronow, Achim; Bianco, María Veronica; Blanco, Federico Carlos; Bleck, Christopher K.E.; Geffers, Robert; Bigi, Fabiana; Abraham, Wolf-Rainer; Gutierrez, Maximiliano Gabriel (Wiley, 2019)
Some intracellular bacteria are known to cause long‐term infections that last decades without compromising the viability of the host. Although of critical importance, the adaptations that intracellular bacteria undergo during this long process of residence in a host cell environment remain obscure. Here, we report a novel experimental approach to study the adaptations of mycobacteria imposed by a long‐term intracellular lifestyle. Selected Mycobacterium bovis BCG through continuous culture in macrophages underwent an adaptation process leading to impaired phenolic glycolipids (PGL) synthesis, improved usage of glucose as a carbon source and accumulation of neutral lipids. These changes correlated with increased survival of mycobacteria in macrophages and mice during re‐infection and also with the specific expression of stress‐ and survival‐related genes. Our findings identify bacterial traits implicated in the establishment of long‐term cellular infections and represent a tool for understanding the physiological states and the environment that bacteria face living in fluctuating intracellular environments.